Swear words used by coastal people of Pidie Aceh - Abdul Manan; Andi Safrizal; Muhammad Arif Fadhilah (Studies in English Language and Education, 2019)
This study was done to find and describe the forms, the references, the meanings, and the purposes of swearing-in Acehnese by the people in Pidie Regency, Aceh, Indonesia. Swearing refers to utterances, usually with negative implications, which are used by people to express their feelings. This qualitative study displays spoken language used by the respondents within the sub-districts of Muara Tiga and Batee in Pidie. The data were processed in three phases: selecting, transcribing and analyzing the appropriate data. The analysis was done by interpreting the forms, references, and purposes of swearing. The forms of swearing were mono-morphemes, poly-morphemes, phrases, clauses, and sentences. Those referred to animals, supernatural beings, religious terms, body parts, family members, human activities, oaths, professions, diseases, and exclamations. The swearing had connotative and denotative meanings to express anger, annoyance, astonishment, insult, and jokes.